Mandibular movement analysis by means of a kinematic model applied to the design of oral appliances for the treatment of obstructive sleep apnea - García Reyes, Marcos; Cabrera Castillo, Juan A.; Bataller-Torras, Alex; Vila, Javier; Mayoral Sanz, Pedro (Elsevier, 2020)
Background: Mandibular advancement devices (MADs) are one of the treatment options used for the obstructive sleep apnea syndrome (OSAS). At present, MADs are designed with standard titration systems, without considering each patient's anatomical characteristics of the temporomandibular joint and mandible shape. The main objective of this study is to evaluate if a variability in mandibular morphology will influence the displacement of the jaw with a MAD. Such knowledge will be of help to find optimal mandibular positions with MAD even when opening the mouth. Methods: By using a mandibular movement model, the movement patterns of different points on the chin have been analyzed. The influence of different skeletal mandibular shapes on these movements have also been studied. The results show differences in the movement patterns of the lower front teeth depending on its distance to the center of the condyle, with a more horizontal direction in those in which there is a greater distance. Results: Variations in mandibular morphology imply differences in movement patterns of the analyzed points of the mandible. Consequently, MADs should be designed according to each patient's anatomy to avoid mandibular retrusion in those areas that may narrow the upper airways. Conclusions: This study may help to understand why not all patients move their lower jaws forwards equally with the same degree of mandibular protrusion measured in relation to the teeth. These results might also partially explain why airway obstruction is more severe in certain untreated sleep apnea subjects than in others when opening their mouth during sleep.
Keywords: Maxilares; Mandíbula; Mandibular movement; Obstructive sleep apnea; Mandibular advancement devices